Microglial Dynamics and Role in the Healthy and Diseased Brain: A Paradigm of Functional Plasticity. (April 2015) - Gomez-Nicola, Diego; Perry, V. Hugh
The study of the dynamics and functions of microglia in the healthy and diseased brain is a matter of intense scientific activity. The application of new techniques and new experimental approaches has allowed the identification of novel microglial functions and the redefinition of classic ones. In this review, we propose the study of microglial functions, rather than their molecular profiles, to better understand and define the roles of these cells in the brain. We review current knowledge on the role of surveillant microglia, proliferating microglia, pruning/neuromodulatory microglia, phagocytic microglia, and inflammatory microglia and the molecular profiles that are associated with these functions. In the remodeling scenario of microglial biology, the analysis of microglial functional states will inform about the roles in health and disease and will guide us to a more precise understanding of the multifaceted roles of this never-resting cells.